Análise da impermeabilização da laje do Palácio do Tribunal de Justiça do Estado de Sergipe - Moura, João Sávio Ferreira (2022)
The waterproofing system aims to protect the building and its systems from the harmful action of water, in order to prevent the appearance of infiltrations and pathologies. Slabs are surfaces that are exposed to these actions, due to the absence, failure of execution and/or maintenance of a waterproofing system. Therefore, this work has the proposal to analyze the execution of a waterproofing system in an exposed concrete slab, being subject to thermal variation and without any type of coverage. To reach this analysis, a bibliographic review was carried out in monographs and academic articles, websites, manufacturers' manuals and monitoring of the execution of the work to check if the procedure performed was within the technical standards. This review understands the importance of the waterproofing system, its types, failures or absence, the pathologies that they can cause and their applications according to the conditions of the slab.